Being a Student in a Village Primary School from an Ethnographic Perspective - Isa GUNGOR; Beyhan Nazli KOCBEKER EID (Anı Publishing, 2021)
This research examined the lifestyle of a typical village settlement and its reflection on the education of children in primary school and the meaning of being a child and student in the village from a sociological perspective. The research aimed to explore how village culture and experiences affect students' educational life in this context. This research was not the product of an external observation, but rather it was based on the impressions and experiences from a teacher's perspective. The ethnographic pattern was preferred because the research focused on examining children's life/learning process within the culture of a village and on the interpretation and reflection of the thoughts and behaviours presented by the people involved in this culture. Observations, participant observations, interviews, and focus group interviews were used in the data collection process. The study revealed that cultural understanding affects many areas. Students and the life experiences of the village have also deeply affected the status of being a student.